Persistent Neurovascular Unit Dysfunction: Pathophysiological Substrate and Trigger for Late-Onset Neurodegeneration After Traumatic Brain Injury - Zhou, Yunxiang; Chen, Qiang; Wang, Yali; Wu, Haijian; Xu, Weilin; Pan, Yuanbo; Gao, Shiqi; Dong, Xiao; Zhang, John H.; Shao, Anwen (Frontiers in Neuroscience, 2020)
Traumatic brain injury (TBI) represents one of the major causes of death worldwide and leads to persisting neurological deficits in many of the survivors. One of the most significant long-term sequelae deriving from TBI is neurodegenerative disease, which is a group of incurable diseases that impose a heavy socio-economic burden. However, mechanisms underlying the increased susceptibility of TBI to neurodegenerative disease remain elusive. The neurovascular unit (NVU) is a functional unit composed of neurons, neuroglia, vascular cells, and the basal lamina matrix. The key role of NVU dysfunction in many central nervous system diseases has been revealed. Studies have proved the presence of prolonged structural and functional abnormalities of the NVU after TBI. Moreover, growing evidence suggests impaired NVU function is also implicated in neurodegenerative diseases. Therefore, we propose the Neurovascular Unit Dysfunction (NVUD) Hypothesis, in which the persistent NVU dysfunction is thought to underlie the development of post-TBI neurodegeneration. We test NVUD Hypothesis through relational inference and direct evidence, and suggest continued NVU abnormalities following TBI serve as pathophysiological substrate and triggers yielding chronic neuroinflammation, proteinopathies and oxidative stress, consequently leading to the progression of neurodegenerative diseases. The NVUD Hypothesis may provide potential treatment and prevention strategies for TBI and late-onset neurodegenerative diseases.